2015
DOI: 10.1007/s00429-015-1024-9
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin signaling in the amygdala modulates reproductive hormone secretion

Abstract: Kisspeptin (encoded by KISS1) is a crucial activator of reproductive function. The role of kisspeptin has been studied extensively within the hypothalamus but little is known about its significance in other areas of the brain. KISS1 and its cognate receptor are expressed in the amygdala, a key limbic brain structure with inhibitory projections to hypothalamic centers involved in gonadotropin secretion. We therefore hypothesized that kisspeptin has effects on neuronal activation and reproductive pathways beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 58 publications
2
63
2
Order By: Relevance
“…In addition to the neuroanatomical data presented here, recent functional studies have shown that kisspeptin signalling in the amygdala regulates gonadotropin secretion [44] . Together, these data provide evidence of a role for the amygdala kisspeptin neurons in the control of the gonadotropic axis, thus integrating limbic circuits and reproductive hormone secretion.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition to the neuroanatomical data presented here, recent functional studies have shown that kisspeptin signalling in the amygdala regulates gonadotropin secretion [44] . Together, these data provide evidence of a role for the amygdala kisspeptin neurons in the control of the gonadotropic axis, thus integrating limbic circuits and reproductive hormone secretion.…”
Section: Discussionsupporting
confidence: 52%
“…We demonstrate here that many kisspeptin neurons are located in the caudal areas of the MePD. The function of kisspeptin neurons in the amygdala is unknown, but the amygdala has been implicated in numerous physiological and behavioural processes, including those related to reward, social behaviours, and reproduction [13][14][15]44] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies will be required to identify the exact cellular substrate in the POA responsive to modulation by MeA Kiss neurons. A decrease in neuronal activity in the POA in association with an increase in LH secretion has been previously reported in response to peripheral administration of kisspeptin [48]. It was proposed that kisspeptin suppresses GABA neurons in the POA to reduce inhibition of GnRH neurons, which leads to increased LH secretion.…”
Section: Discussionmentioning
confidence: 80%
“…Direct intra-amygdala injection of kisspeptin results in increased LH secretion, while conversely blocking endogenous amygdala kisspeptin signalling with a kisspeptin antagonist decreases both LH secretion and LH pulsatility [25], clearly demonstrating the influence of kisspeptin signalling outside the hypothalamus on the HPG axis.…”
Section: Kisspeptin Signalling Outside the Hypothalamusmentioning
confidence: 98%